Evaluating multi-sensor data for the development of three-dimensional photo realistic model of archaeological site documentation [electronic resource] - Nurul Shahida Sulaiman, 1987- author; Halim Setan, supervisor; Zulkepli Majid; Fakulti Geoinformasi dan Harta Tanah (2014)
Thesis (Sarjana Sains (Kejuruteraan Geomatik)) - Universiti Teknologi Malaysia, 2014